Convergence regions for multiple hypergeometric inegrals representing h-function in several variables - Hai, Nguyen Thanh (Integral transforms and special functions, 1993)
Convergence regions for multiple Mellin-Barnes contour integrals represening hypergeometric H-functions in several variables is described